2002
DOI: 10.1128/jvi.76.17.8963-8965.2002
|View full text |Cite
|
Sign up to set email alerts
|

Decelerating Decay of Latently Infected Cells during Prolonged Therapy for Human Immunodeficiency Virus Type 1 Infection

Abstract: Antiviral therapy induces a rapid drop in human immunodeficiency virus type 1 viremia, but the decline of virus levels decelerates over time. Mathematical modeling demonstrates that the source of residual virus production might be a single compartment of latently infected cells with an extended distribution of activation rates.The rapid initial decline of virus levels after the initiation of highly active antiretroviral therapy (HAART) reflects the decline of productively infected CD4 ϩ T cells (15,18,24). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…The change in clearance kinetics might reflect decreasing activation rates after viral suppression [48]. Alternatively, cells recognizing common antigens may be preferentially activated and cleared during the first year, leaving latently infected memory cells that recognize rarely encountered antigens to activate slowly in subsequent years [10,49]. The different dynamics of phenotypically distinct populations of long-lived cells, including memory T cells, naive T cells [50], thymocytes, and other cell types [51][52][53], might also contribute to the decline in clearance.…”
Section: Discussionmentioning
confidence: 98%
“…The change in clearance kinetics might reflect decreasing activation rates after viral suppression [48]. Alternatively, cells recognizing common antigens may be preferentially activated and cleared during the first year, leaving latently infected memory cells that recognize rarely encountered antigens to activate slowly in subsequent years [10,49]. The different dynamics of phenotypically distinct populations of long-lived cells, including memory T cells, naive T cells [50], thymocytes, and other cell types [51][52][53], might also contribute to the decline in clearance.…”
Section: Discussionmentioning
confidence: 98%
“…Perhaps memory lymphocytes, which recognize a spectrum of antigens, activate and clear at a continuum of rates according to antigen specificities and the abundance of cognate antigens (44,45). The selective enrichment of HIV-infected cells recognizing rarely encountered antigens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that a pool of latently infected cells is established during the primary phase of HIV infection (Bonhoeffer et al, 1997;Grossman et al, 1998;Havlir et al, 2003;Lafeuillade et al, 2000;Muller et al, 2002). These cells are infected cells in a resting state and can be activated after a long time of dormancy to produce infectious virus particles.…”
Section: Modeling Latently Infected Cellsmentioning
confidence: 99%